The fundamental principles of CMF design colour, material, finish - Becerra, Liliana (Frame Publishers, 2016)
"Introducing the CMF process and detailing the areas of colour, finish and material design, this book serves as a valuable source of information about this emerging professional discipline and its fundamental principles -- back cover